The influence of chitin-urea amendments applied to an organic soil on a Meloidogyne hapla population and on the growth of greenhouse tomato - Bélair, G.; Tremblay, N. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
This experiment was conducted under greenhouse conditions to evaluate the efficiency of chitin-urea amendments to an organic soil against a Quebec population of the northern root-knot nematode (Meloidogyne hapla) and to assess the pathogenicity of this population on tomato (Lycopersicon esculentum). Chitin-urea amendments at 0.2 and 0.4% (vol:vol) were ineffective in reducing the preplant nematode populations. The final M. hapla egg populations were significantly increased in chitin-urea amended soils, and a signifiant positive dosage effect was recorded. Shoot growth of tomato plants was significantly reduced by M. hapla but was increased by chitin-urea. At harvest, fruit weights were neither affected by M. hapla nor by chitin-urea amendments. The final M. hapla egg population was linked to lower N and P levels, and to higher Ca levels in leaf tissues.